Sifat Kimia dan Warna Kayu Teras Jati pada Tiga Umur Berbeda Chemical and Colour Properties of Teak Heartwood from Three Different Ages - Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2009)
Teak (Tectona grandis L.f.) wood has gained its high reputation for natural durability, weather resistance, and appearance. The heartwood quality of 15, 25, and 72-year-old teak trees from forest plantation was assessed in relation to chemical and colour properties. With tree age, an increasing tendency was found in the ethanol-benzene and water soluble extractive contents, whereas a decreasing tendency was observed in the pH value. Furthermore, from the ethanol-benzene components, the contents of tectoquinone, squalene, and total quinone increased with age. With regard to the colour properties, the brightness (L*), yellowness (b*), hue (h), and chroma (C*) levels tended to decrease while the redness (a*) level fluctuated with tree age